Aid to the West Indies - Morgan, David John. (London : Overseas Development Institute, 1964)
The main aim of the author of this pamphlet was to study banking developments of the West Indies and discuss problems of obtaining and using British aid.
Includes bibliographical footnotes.
ne 27/08/2019
Loans
Keywords: Economic assistance, British; Technical assistance, British